Effect of fungicide farmayod on agrotechnical and technological indicators of grapevine, on viral diseases and oidium - Sirotkina Nadezda (E3S Web of Conferences, 2021)
The paper presents the study on the effect of Farmayod’s GR (100 g/l of iodine) spraying on vineyards of Cabernet Sauvignon and Baklanovsky varieties on the degree of viral and oidium prevalence as well as on agrobiological and technological indicators. According to the aggregate agrobiological and technological indicators, the best results on Cabernet Sauvignon variety were obtained when the drug was used at a concentration of 0.06 %. On the Baklanovsky variety the best indicators were obtained at a drug concentration of 0.04%. Testing of plant samples for the presence of Grapevine fan leaf virus, Arabis mosaic virus and Oidium tuckeri showed that after two years of applying the drug, the prevalence of infected plants (P, %) with Grapevine fanleaf virus on the Cabernet Sauvignon cultivar varied from 0% (fungicide concentration 0.04 and 0.05 %) to 0.8 % (0.06 %) and 2.65 % (control). For Baklanovsky variety: Grapevine fanleaf virus - concentration 0.04 % - 1.8; 0.05 % - 0.4; 0.06 % - 2.0; control - 2.65 %. Arabis mosaic virus – 0; 0; 3.0; 12.1 %, respectively. Oidium tuckeri was 0 % in all variants with any drug concentrations. Control variant and later 80 % for 29.09.